Preparation and quality evaluation of amoxicillin polybutylcyanoacrylate nanoparticles - YANG Xue-feng; OUYANG Wu-qing; LIU Yu-mei; ZHANG Wen-juan; SUN Jiang-cai (浙江大学学报. 农业与生命科学版)
Amoxicillin polybutylcyanoacrylate nanoparticles (AMX-PBCA-NP) were prepared by the emulsion polymerization method with butylcyanoacrylate (BCA) as a carrier material. The preparation procedure was optimized according to the results of single factor experiments and uniform design tests, and then the quality of AMX-PBCA-NP was evaluated. The results show that the screened optimum conditions for the preparation of AMX-PBCA-NP were 4 g·L-1 amoxicillin, 10 mL·L-1 BCA, 10 g·L-1 pluronic F68, 10 g·L-1 dextran-70 and pH 3.0. The prepared nanoparticles were globular, unconglutinate, well-distributed. The mean diameter of the particles was (222.33±1.53) nm, polydispersity index was 0.03±0.02, the mean encapsulation ratio and drug-load was (73.47±0.96)% and (29.39±0.38)%, respectively. The release characteristics in vitro were consistent with two phases kinetics rule. The minimal inhibitory concentration (MIC) against E. coli ATCC25922 and S. aureus ATCC25923 was 1/2 times of the MIC of active pharmaceutical ingredients, respectively. The results above suggested that the optimal preparation procedure of AMX-PBCA-NP is practicable, AMX-PBCA-NP has the slow-release character and the antibacterial activity of amoxicillin is enhanced in vitro.